A Visual-Based Energy Efficient Chatbot: Relationship between Sentiment Analysis and Customer Satisfaction - Johari N.M.; Zaman H.B.; Baharin H.; Nohuddin P.N.E. (Springer Science and Business Media Deutschland GmbH, 2025)
The evolution of Chatbots today has been seen to be popular in various service sectors such as education, business, as well as banking. The assistance provided by the system has been able to ease the tasks that otherwise need to be done by human agents. This paper highlights the development of the visual-based energy efficient Chatbot (VBE2Chatbot), testing, and explores the changes of sentiment projected by the end user during the pre-survey stage and post-survey stage. The visual-based and energy efficient Chatbot system refers to one that is designed using visual elements (such as images, videos, or graphical interfaces) to enhance user experience whilst being optimized for energy efficient (optimising code, server-side processing, smart wake-up and sleep modes and caching). This paper also highlights the findings of sentiment analysis based on customer satisfaction. On the whole, findings of the study showed positive results on its satisfaction based on the design and development of a visual-based energy efficient Chatbot (VBE2Chatbot). More work needs to be conducted to integrate AI, visual elements, and energy efficient elements into the VBE2Chatbot. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.